Identifying factors influencing employee turnover intention in Malaysian Small and Medium-sized Enterprises (SMEs) restaurants - Ghazali, Hazrina; Misbahwazir, Fatin Nabilah; Abu Bakar, Ainul Zakiah; Ismail, Ahmad Fareed (RSIS International, 2024)
The restaurant industry in Malaysia is one of a vital component of the country's economy, generating employment, attracting tourists, and showcasing rich cultural experiences. In recent years, the restaurant industry has experienced significant expansion, with small and medium-sized restaurants (SMEs) emerging as major contributors to Malaysia's economic growth. However, along with the growth and opportunities one of the persistent challenges faced by SMEs restaurants is high turnover rates among their employees. Therefore, the objectives of this research are to identify the potential factors that influence employee turnover intention in SMEs restaurant in Klang Valley. In addition, this study also determines the most influential factor that causes employees’ turnover intention in SMEs Restaurant in Klang Valley. Next, the last research objective of this study is to examine the relationships between predicted variables and employees’ turnover intention. The factors used to conduct this study are job satisfaction, job stress, organizational commitment and person-organization fit. The research design for this study was constructed using a quantitative approach through a self-administered survey questionnaire. Data obtained were analysed by using Statistical Package for the Social Sciences (SPSS) version 27. The results of job satisfaction (mean=3.58), job stress (mean=3.19), organizational commitment (mean=3.25) and person-organization fit (mean=3.52) indicate a score leaning towards agreement on predicted variables. Furthermore, the findings revealed that job satisfaction and job stress had a moderate relationship with employees’ turnover intention, while organizational commitment and person-organization fit had a weak relationship. Multiple Linear Regression Analysis revealed that job stress is the most influential factor of employees' intention to leave their job, with a coefficient of 0.450, followed by job satisfaction being the second most influential factor with coefficient of -0.301 and person-organization fit (-0.158). Findings of this study are hoped to help the owner of restaurant, the manager or department head to aware of and tolerant of potential contributing causes to employees' intention to leave the organization. Findings also expected to provide management with a better perspective and direction in implementing an effort to reduce and minimize employee turnover intention and ultimately creating productive workplace.